2021
DOI: 10.7566/jpsj.90.063702
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of Superlattice Reflections in the Hidden Order at 105 K of Spin–Orbit Coupled Iridium Oxide Ca5Ir3O12

Abstract: We report the inelastic X-ray scattering (IXS) experimental results of iridium oxide Ca 5 Ir 3 O 12 with a strong spin-orbit interaction, showing the hidden order at 105 K where no superlattice reflections were observed so far. We measured the IXS spectra of Ca 5 Ir 3 O 12 along Γ-A, Γ-M, Γ-K-M, M-L, and K-H directions in the Brillouin zone of a hexagonal lattice down to 20 K. The obtained phonon spectra show almost no change on cooling; there are no soft phonon modes. However, the superlattice reflections spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Since we have found that the antisymmetric thermopolarization is attributed to the appearance of the ferrotype electric-toroidal dipole order, the compounds with the ferroaxial order for lattice distortions potentially exhibit nonzero antisymmetric thermopolarization. The candidate materials are listed as CaMn 7 O 12 [34], NiTiO 3 [53], RbFe(MoO 4 ) 2 [54], and Ca 5 Ir 3 O 12 [71]. It is desired to search other materials exhibiting electric-toroidal dipole orders in the electronic origin, which might be controllable via the degrees of freedom intrinsic to electrons, such as charge and spin.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have found that the antisymmetric thermopolarization is attributed to the appearance of the ferrotype electric-toroidal dipole order, the compounds with the ferroaxial order for lattice distortions potentially exhibit nonzero antisymmetric thermopolarization. The candidate materials are listed as CaMn 7 O 12 [34], NiTiO 3 [53], RbFe(MoO 4 ) 2 [54], and Ca 5 Ir 3 O 12 [71]. It is desired to search other materials exhibiting electric-toroidal dipole orders in the electronic origin, which might be controllable via the degrees of freedom intrinsic to electrons, such as charge and spin.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be observed in the materials with the ferro-type electric-toroidal dipole order. The candidate materials are the compounds with the ferroaxial order for lattice distortions, such as CaMn 7 O 12 [26], NiTiO 3 [45], RbFe(MoO 4 ) 2 [46], and Ca 5 Ir 3 O 12 [61]. It is desired to search other materials exhibiting electric-toroidal dipole orders in the electronic origin, which might be controllable via the degrees of freedom intrinsic to electrons, such as charge and spin.…”
Section: Discussionmentioning
confidence: 99%
“…90,91) Among them, the atomic multipoles belonging to the E + representation can construct the A + 2 representation corresponding to the ETD within a triangular cluster. Thus, the Hilbert space should include such multipole degrees of freedom belonging to the E + representation to describe the ETD ordering observed in 82) where each triangle unit of the Ir ions is supposed to have the ETD based on the Raman scattering experiments. 80) Based on this symmetry analysis, we consider an effective model to include the multipoles under the E + representation.…”
Section: Mp Rank Basismentioning
confidence: 99%
“…Ca 5 Ir 3 O 12 has a hexagonal structure (P 62m), which might be a prototype to possess both ETD and MTQ, as will be discussed. This material undergoes two phase transitions at 105 K and 7.8 K: 78,79) The former transition was identified as the onset of the ETD ordering with the √ 3a × √ 3a × 3c superstructure in the hexagonal coordinate, [80][81][82] although relevant electronic degrees of freedom for the ETD ordering have been still lacking. The latter was identified as the antiferromagnetic ordering, [83][84][85] where a detailed structure has not been revealed; no magnetic reflections have been observed by powder neutron diffraction experiments 86) and a possibility of multipole magnetic ordering was implied, 85) which is similar to the hidden order in URu 2 Si 2 .…”
mentioning
confidence: 99%